2011
DOI: 10.1182/asheducation-2011.1.427
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Prevention of Overt Strokes in Sickle Cell Disease: Therapeutic Strategies and Efficacy

Abstract: Overt strokes, previously one of the most common neurological complications in sickle cell disease (SCD), have become far less frequent with routine transcranial Doppler (TCD) assessment followed by regular blood transfusion therapy. Nevertheless, children and adults with SCD continue to have overt strokes, and in the foreseeable future will continue to require secondary prevention of strokes. With the exception of the most recently completed "Stroke With Transfusions Changing to Hydroxyurea" Trial (SWiTCH; NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…17,48,49 Table 1 provides the checklist we use when organizing an exchange transfusion therapy in an individual with focal neurologic deficit. 50 In adult patients with SCD presenting with acute ischemic stroke, the preferred initial approach remains an exchange transfusion because of the very high risk of recurrent cerebral infarcts. There is an ;50% recurrence rate in the first 2 years if no treatment is initiated.…”
Section: -29mentioning
confidence: 99%
“…17,48,49 Table 1 provides the checklist we use when organizing an exchange transfusion therapy in an individual with focal neurologic deficit. 50 In adult patients with SCD presenting with acute ischemic stroke, the preferred initial approach remains an exchange transfusion because of the very high risk of recurrent cerebral infarcts. There is an ;50% recurrence rate in the first 2 years if no treatment is initiated.…”
Section: -29mentioning
confidence: 99%
“…8,15 In those children and adults who have experienced prior stroke or children at risk of initial stroke based on elevated TCD velocity, chronic blood transfusion is the standard of care to prevent recurrence or initial stroke. 54 Findings from the SWiTCH trial add support to this recommendation. The upcoming TCD with Transfusions Changing to Hydroxyurea (TWiTCH) study is a National Heart Lung and Blood Institute (NHLBI)-sponsored, phase 3, multicenter trial that will compare monthly transfusions, the current established treatment, to daily hydroxyurea to reduce the risk of primary stroke in children with SCA and abnormal TCD velocities.…”
Section: Discussionmentioning
confidence: 67%
“…Sickle Cell Disease (SCD) AIS occurs in 11 % of children with SCD by age of 20 y (peak age of onset 2-5 y) [30,31]. Fifty percent have a second stroke within 2 y [30].…”
Section: Moyamoya Arteriopathymentioning
confidence: 99%
“…In addition to the general neuroprotective measures for AIS, supportive measures include oxygen and red blood cell (RBC) transfusion. Exchange RBC transfusion is generally the preferred option [31,33]. Randomized control trials have demonstrated that long term chronic monthly RBC transfusion (goal of maintaining HbS <30 %) significantly prevents recurrent stroke and is currently recommended after first stroke in SCD and when transcranial Doppler velocity exceeds 200 cm/s in the MCA [32].…”
Section: Moyamoya Arteriopathymentioning
confidence: 99%
See 1 more Smart Citation